Non-transferrin bound iron: A key role in iron overload and iron toxicity - Brissot, Pierre; Ropert, Martine; Le Lan, Caroline; Loréal, Olivier (Biochimica et biophysica acta, 2012)
Besides transferrin iron, which represents the normal form of circulating iron, non-transferrin bound iron (NTBI) has been identified in the plasma of patients with various pathological conditions in which transferrin saturation is significantly elevated. To show that: i) NTBI is present not only during chronic iron overload disorders (hemochromatosis, transfusional iron overload) but also in miscellaneous diseases which are not primarily iron overloaded conditions; ii) this iron species represents a potentially toxic iron form due to its high propensity to induce reactive oxygen species and is responsible for cellular damage not only at the plasma membrane level but also towards different intracellular organelles; iii) the NTBI concept may be expanded to include intracytosolic iron forms which are not linked to ferritin, the major storage protein which exerts, at the cellular level, the same type of protective effect towards the intracellular environment as transferrin in the plasma. Plasma NTBI and especially labile plasma iron determinations represent a new important biological tool since elimination of this toxic iron species is a major therapeutic goal. The NTBI approach represents an important mechanistic concept for explaining cellular iron excess and toxicity and provides new important biochemical diagnostic tools. This article is part of a Special Issue entitled Transferrins: Molecular mechanisms of iron transport and disorders. ► NTBI and its toxic form LPI appear in plasma when transferrin saturation increases. ► NTBI is avidly taken up by parenchymal cells (especially hepatocytes). ► Labile Iron Pool can be considered as an intracytosolic equivalent of plasma NTBI. ► NTBI can be present in diseases not primarily related to iron overload. ► Therapeutic efforts (phlebotomies, iron chelation) must focus on NTBI elimination.